Treatment of menstrual disorders: a shift from synthetic drugs to drugs of natural origin - VISHAKHA DEORAY; AMIT PAGE (International Journal of Pharma and Bio Sciences, 2018)
As our lifestyle changes, we have to face number of diseases or disorders, especially in case of the women. They face various gynecological problems like the menstrual disorders. Menstruation often brings various uncomfortable symptoms such as mild cramps and fatigue. These problems usually go away when periods begin. Sometimes more serious menstrual problems arise such as complete absence of menstrual cycle, dysmenorrhea, menorrhagia, amenorrhea, oligomenorrhea and premenstrual syndrome. All these problems are signs of abnormal menstrual cycle. Present day drugs, available for treatment of these problems, have one thing in common – they act through the hormonal regulation. This interference in hormonal regulation by these drugs can result in overall hormonal imbalance, which invites other associated health problems. Hence, the focus of the treatment of menstrual disorders and related diseases is shifting from synthetic drugs to the drugs of natural origin. In our ancient ayurvedic system, some plants or shrubs which have the medicinal properties are used to treat such type of gynecological disorders. In this present review we attempt to give an overview of the causes of the menstrual disorders and provide insights to natural drugs in the pipeline for such a treatment.